Subjected words : African linguistics and the colonial encounter - (:unkn) unknown (My University, 2015)
RESUME - TRADUCTION :Il s'agit d'une contraction (21 p. > 6p .) en français de l'article de Judith T. Irvine (2008) "Subjected words : African linguistics and the colonial encounter", Language and communication 28, p. 323-343.
Keywords: African Research